Divorce: Counseling Guidance for Students Affected in Parents Divorce - Susana; Imam Tabroni (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
This study aims to find out the impact of parental divorce on the psychological development of students in the Madrasah Tsanawiyah Yakpi Kalijati Subang Regency. The research was conducted using a qualitative approach with descriptive methods. The results obtained by researchers in the field are that there is an unfavorable impact on the development of students from a cognitive perspective. This side experiences a decrease in the level of critical thinking and analysis. Children tend to surrender and do not want to try analytical thinking processes to ask questions and find certain ideas. Affective. Depressed and emotional attitudes are often shown by students who are affected by divorce, they cannot accept that fact because they still need the love of both. Psychomotor, this aspect is often seen when the learning process takes place, blank stares and silence without language is a fact that psychomotor does not work optimally. For this reason, researchers hold intensive communication with these students with the intention of creating a progressive emotional relationship between educators and students.